O fundamento da misericórdia para a compreensão de Deus e do ser humano - Auzani, Mário Benachio (2018)
The present research deals with the biblical category of “mercy” as an essential foundation of Christian life. It uses biblical commentary from the Old and New Testaments to verify the strength of origin. In a second moment it resorts to the philosophical reflection of Emmanuel Levinas, a contemporary Jewish thinker who has elaborated the biblical category of mercy in anthropological and ethical terms. Finally, the dissertation draws on the pontifical teaching of John XXIII, John Paul II and pope Francis, summarized in three perspectives: a merciful Church, a merciful God, mercy is the very name of God.